Evaluation of genetic diversity of Cryptococcus neoformans samples isolated in different geographical regions (Research, Society and Development, 2021)
Cryptococcus neoformans is the etiological agent of cryptococcosis, an opportunistic fungal infection and frequently occurs in immunocompromised patients, with an underlying disease, mainly affecting the central nervous system and lungs. Analysis of genomic sequences of microorganisms through phylogenies has demonstrated a wide spectrum of applications in scientific research and medicine. In the health area, the use of this tool contributes to the diagnosis and consequently to the development of programs to improve the treatment and control of diseases. Furthermore, the phylogenetic analysis is important to characterize new species that can development possible genetic recombinations, which in most cases is responsible for the resistance of pathogens to the treatment. Thus, this study aimed to analyze the genetic variability of 18S and 28S genes of C. neoformans in different geographic regions. Were selected 191 sequences of the 18S gene and 132 sequences of the 28S gene to carry out phylogenetic and split analyses. The results demonstrated that the 28S gene has more genetic variability when compared to the 18S gene, which has been shown to be more conserved. This variability can be a result from genetic recombination and migration of different strains from one geographic region to another through the tourism of individuals with the fungal. Additionally, in the future, this genetic recombination can result in a new species capable of causing diseases in humans.